Electronic structure of large modified nickel nanoclusters - Pokhmurskii, V.; Kopylets, V.; Korniy, S. (Condensed Matter Physics, 2006)
A combined method of quantum-chemical semiempirical approach MNDO and molecular dynamics with atomic potentials was used while studying the growth of large nanoclusters of nickel. Geometry and electronic structure of Ni₄₈₅ were studied as well as a series of similar surface (111) substituted (by Pd, Pt, Cu, Mn and Cr) clusters. The role was analysed of the surface electronic density of states (DOS) and their contribution into the processes such as adsorption and surface reaction at catalytic oxidation of carbon monoxide. Stability of all substituted nanoclusters was analyzed and surface electron charges were estimated as negligible in agreement with experiments and exact calculations by periodic ab initio methods.